2012
DOI: 10.1002/gea.21406
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Paleogeographic Conditions at TwoPaleolithic Sites inNavarino, SouthwestGreece, Dated by Optically Stimulated Luminescence

Abstract: In this paper, we employed optically stimulated luminescence (OSL) dating of sediments from two archaeological sites located in Navarino, Messenia, southwestern Greece, to deduce a chronology for the archaeological sites. Archaeological surveys identified two Paleolithic sites on fossilized coastal dunes. Chipped stone tool assemblages were identified eroding out of paleosols developed in the dunes. The assemblage from one site lacked distinct typological features and hence it was difficult to assign to a chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 76 publications
(158 reference statements)
0
8
0
Order By: Relevance
“…Laboratory measurements of electron-retention lifetimes for the TT-OSL source trap suggest that significant age underestimations might be expected for Early Pleistocene samples depending on long-term burial temperatures (e.g., 10% underestimation for a 1 Ma sample buried at 10 C and more than 50% underestimation for a 1 Ma sample buried at 20 C; Adamiec et al, 2010). Apparent TT-OSL age underestimations have been observed in certain empirical studies (e.g., Athanassas et al, 2012). However, other studies of independently (or semi-independently) dated samples have not definitely shown that such predicted TT-OSL age underestimations exist when taking into account dating uncertainties (e.g.…”
Section: Introductionmentioning
confidence: 95%
“…Laboratory measurements of electron-retention lifetimes for the TT-OSL source trap suggest that significant age underestimations might be expected for Early Pleistocene samples depending on long-term burial temperatures (e.g., 10% underestimation for a 1 Ma sample buried at 10 C and more than 50% underestimation for a 1 Ma sample buried at 20 C; Adamiec et al, 2010). Apparent TT-OSL age underestimations have been observed in certain empirical studies (e.g., Athanassas et al, 2012). However, other studies of independently (or semi-independently) dated samples have not definitely shown that such predicted TT-OSL age underestimations exist when taking into account dating uncertainties (e.g.…”
Section: Introductionmentioning
confidence: 95%
“…OSL dating of the buried sediments can be used to determine the maximum age of the collapse and related earthquakes. Luminescence is a widely used technique for dating both archaeological and geological materials (Huntley, Godfrey‐Smith, & Thewalt, ; Spooner et al., ; Yanchou et al., ; Atlıhan & Meric, ; Athanassas et al., ).…”
Section: Osl Datingmentioning
confidence: 99%
“…This study in the Mariana Islands illustrates how to find ancient habitation layers in paleo-beaches that now are buried under some meters of sediments and stranded far inland from their original shoreline-oriented contexts. A similar approach can be applied in other regions, for example as others have done in reconstructing coastlines of California (Masters & Aiello, 2007), lost Pleistocene landscapes of the English Channel (Sturt, Garrow, & Bradley, 2013), and several studies of the paleo-geography surrounding the Mediterranean Sea (Athanassas et al, 2012;Kızıldag,Özdas, & Ulug, A 2012;Stanley & Bernasconi, 2012). Numerous other examples exist, but a full review is outside the scope of this brief illustrative example.…”
Section: Introductionmentioning
confidence: 98%
“…A similar approach can be applied in other regions, for example as others have done in reconstructing coastlines of California (Masters & Aiello, 2007), lost Pleistocene landscapes of the English Channel (Sturt, Garrow, & Bradley, 2013), and several studies of the paleo-geography surrounding the Mediterranean Sea (Athanassas et al, 2012;Kızıldag,Özdas, & Ulug, A 2012;Stanley & Bernasconi, 2012). A similar approach can be applied in other regions, for example as others have done in reconstructing coastlines of California (Masters & Aiello, 2007), lost Pleistocene landscapes of the English Channel (Sturt, Garrow, & Bradley, 2013), and several studies of the paleo-geography surrounding the Mediterranean Sea (Athanassas et al, 2012;Kızıldag,Özdas, & Ulug, A 2012;Stanley & Bernasconi, 2012).…”
Section: Introductionmentioning
confidence: 99%